Ungkapan Makian Bahasa Minangkabau di Kenagarian Taluk Kecamatan Lintau Buo Kabupaten Tanah Datar - Refmiyanti, Refmiyanti; Agustina, Agustina; Gani, Erizal (Universitas Negeri Padang, 2012)
The purpose of this study was to describe the form, context and function of invective in the language of Minangkabau expression for people in Kenagarian Taluk District Lintau Buo Tanah Datar. The data of this study is the expression of Minangkabau people cuss at Kenagarian Taluk District Lintau Buo Tanah Datar. The data source is a primary source of oral sources as told by informants as the original speakers. Data collected using recording techniques, observing techniques, and techniques of record as advanced techniques. The study's findings include three things: (1) based on the form, can be classified into two types, expressing cursc which used by the society found in the form of words and phrases, (2) based on the context, it was found that in the two contexts or upset and emotional state in joking situation (3) based on the functions found eight: expressing resentment, express strong emotions and extreme, as a joke or comedy purposes, express intimacy in relationships, contempt, express achievement and irritated, threat and, as a means of disclosure astonishment.